Efektifitas Model Community As Partner dalam Memberikan Asuhan Keperawatan Komunitas pada Kelompok Balita dengan Gizi Buruk di Kelurahan Pancoran Mas, Kota Depok - titih huriah (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2007)
The prevalence rate of under-five children with poor nutritional status in Indonesia has been increasing. This also happens in Depok City, particularly in Pancoran Mas Village, wherein the prevalence rate of under-five children with poor nutritional status in 2005 reached 1.67% or there were 88 under-five children with poor nutritional status among 5249 under- five children. This study aimed to evaluating the effectiveness of the application of community nursing concept and theory in order to improve health services through community nursing care particularly in under-five children group with poor nutritional status in Pancoran Mas Village, Depok. This was a quasi experiment research using a non-randomized pretest-posttest control group design. Data collection was done using observation, interview, focus group discussion (FGD) dan questionaire. Research instruments used included food journal of under-five children within 24 hours, physical examination guideline, interview guideline, FGD guideline and questionaire. The questionaire was developed based on Community as a Partner Model. Research population was 44 mothers who had under-five children with poor nutritional status in Pancoran Mas Village. Research sample was 30 mothers who had under-five children with poor nutritional status who fulfilled the inlcusion criteria. Primary, seconadry dan tertiary interventions were done to the 30 mothers within 9 months. Evaluation after the implementation of serial community nursing interventions showed that there was an increase in knowledge about nutrition and poor nutrition from 46% to 92%, an increase in attitude from 60% to 96%, and an increase in family skill in meeting the nutrition requirement for under-five children with poor nutritional status from 30% to 85%. Furthermore, there was improvement of nutritional status i.e. from 27 under-five children with poor nutritional status, after interventions they improved to 1 child with poor nutritional status, 19 children with low nutritional status and 12 children with good nutritional status; whereas five children with low nutritional status improved to good nutritional status.Angka prevalensi kasus gizi buruk pada balita di Indonesia semakin menunjukkan peningkatan. Hal ini juga terjadi di Kota Depok khususnya di Kelurahan Pancoran Mas, di mana angka prevalensi gizi buruk pada balita pada tahun 2005 mencapai 1,67% atau terdapat 88 balita gizi buruk dari 5249 balita. Tujuan penelitian ini adalah menilai keefektifan aplikasi teori dan konsep keperawatan komunitas dalam rangka meningkatkan pelayanan kesehatan melalui asuhan keperawatan komunitas khususnya pada kelompok balita dengan gizi buruk di Kelurahan Pancoran Mas Depok. Penelitian ini adalah eksperimen semu atau quasi eksperimental menggunakan desain non- randomizedpretest-posttest control group. Pengumpulan data dilakukan dengan observasi, wawancara, focus group discussion (FGD) dan kuesioner: Alat yang digunakan adalah catatan makanan balita selama 24 jam, pedoman pemeriksaan fisik, pedoman wawancara, pedoman FGD, dan kuesioner. Kuesioner disusun berdasarkan Community as a Partner Model. Populasi penelitian adalah 44 ibu yang memiliki balita dengan gizi buruk di Kelurahan Pancoran Mas Depok. Sampel penelitian adalah 30 ibu yang mempunyai balita dengan gizi buruk yang memenuhi kriteria inklusi. Pada 30 ibu tersebut dilakukan intervensi primer, sekunder dan tertier selama 9 bulan. Evaluasi setelah pelaksanaan rangkaian kegiatan keperawatan komunitas menunjukkan bahwa terjadi peningkatan pengetahuan tentang gizi dan gizi buruk dari 46% menjadi 92%, peningkatan sikap dari 60% menjadi 96% dan peningkatan keterampilan keluarga dalam memenuhi kebutuhan gizi pada balita gizi buruk dari 30% menjadi 85%. Selain itu, terjadi perbaikan status gizi yaitu dari 27 balita gizi buruk, setelah intervensi menjadi 1 balita gizi buruk, 19 gizi kurang dan 12 gizi baik. Sedangkan dari lima balita gizi kurang telah meningkat menjadi gizi baik.